JURIDICAL ANALYSIS OF THE DECISION OF THE CONSTITUTIONAL COURT NUMBER 91/PUU-XVIII/2020 ON LAW NUMBER 11 YEAR 2020 - Syofyan, Yunita; Nazmi, Didi (Universitas Ekasakti, 2023)
The interest of the people is the formation of rules that are able to accommodate the eye of the law. Article 20 paragraph (1) of the 1945 Constitution states that